You shouldn't have shut them out: Justice sensitivity and norm adherence affect moral reactions to observed ostracism. (February 2023) - Rudert, Selma C.; Speckert, Kristina
Abstract: In ostracism situations, the role of uninvolved observers is a crucial one, as observers can decide to either support the ostracized target or the ostracizing sources. Previous research has established the important role of target norm adherence for observer's moral judgment and reactions to ostracism. Here, we extend this line of research to investigate the moderating effects of observers' dispositional justice sensitivity. Two experimental studies show that justice sensitivity moderates the effects of target norm adherence on observers' moral judgments, moral emotions, and punitive behavior. Particularly, individuals tended to show stronger negative reactions towards the target and less negative reactions towards the sources if the target had violated a social norm (and vice versa if the target had acted norm-consistently). This effect was more pronounced for observers high (vs. low) in observer justice sensitivity. The results emphasize the role of trait justice sensitivity in moral reactions to observed ostracism episodes. Highlights: Observers of ostracism will decide to either side with the sources or the target. Target norm adherence drives observers' moral reactions to sources and target. The effect is stronger for individuals high in observer justice sensitivity. Findings have implication for moral courage of bystanders in ostracism situations.